Reading Comprehension and Working Memory's Executive Processes: An Intervention Study in Primary School Students. Issue 2 (1st April 2013) - García‐Madruga, Juan A.; Elosúa, María Rosa; Gil, Laura; Gómez‐Veiga, Isabel; Vila, José Óscar; Orjales, Isabel; Contreras, Antonio; Rodríguez, Raquel; Melero, María Ángeles; Duque, Gonzalo
Abstract Reading comprehension is a highly demanding task that involves the simultaneous process of extracting and constructing meaning in which working memory's executive processes play a crucial role. In this article, a training program on working memory's executive processes to improve reading comprehension is presented and empirically tested in two experiments with third‐grade primary school students. Experiment 1 showed a greater gain after training the experimental group in contrast to the control group in reading comprehension and intelligence. In experiment 2, we focused on the training processes and compared training results of high and low pretest reading comprehension groups. Results confirmed the increase in reading comprehension, intelligence, and executive processes and showed that the low group reached a greater gain in reading comprehension after training than the high group did. The results of these experiments and their limitations are discussed in the context of recent theories on the role of executive processes in reading comprehension and the possibility of training working memory and intelligence.